ІННОВАЦІЙНІ ПІДХОДИ ДО ОРГАНІЗАЦІЇ КОМУНІКАЦІЙ НА РИНКУ МЕДИЧНИХ ПОСЛУГ (ІННОВАЦІЙНА ЕКОНОМІКА, 2022)
Котис Н.В., Мацик В.О. ІННОВАЦІЙНІ ПІДХОДИ ДО ОРГАНІЗАЦІЇ КОМУНІКАЦІЙ НА РИНКУ МЕДИЧНИХ ПОСЛУГМета. Узагальнення сутності, місця та особливостей комунікацій на ринку медичних послуг та обґрунтування доцільності використання інноваційних підходів до організації комунікаційної діяльності закладів охорони здоров’я.Методика дослідження. Теоретичною і методологічною основою статті є фундаментальні положення сучасної економічної науки. У процесі дослідження використані наступні методи: теоретичного узагальнення та наукової абстракції – при обґрунтуванні категоріально-понятійного апарату дослідження; системного аналізу – при формуванні теоретико-методологічної бази та структури дослідження; метод порівняльного аналізу – при виявленні закономірностей і просторових відмінностей в організації комунікацій медичних установ; методи описової статистики та візуального аналізу – для наочного представлення основних положень дослідження; описового та концептуального моделювання – для представлення комплексної системи комунікацій закладу охорони здоров’я. Результати дослідження. Акцентовано увагу на зростаючій ролі комунікацій на ринку медичних послуг. Визначено сутність та особливості медичних послуг. Ідентифіковано засади формування вітчизняного ринку медичних послуг та проаналізовано його специфіку. Визначено особовості медичних комунікацій та комунікаційні проблеми закладів охорони здоров’я. Проаналізовано тенденції розвитку сучасних комунікаційних технологій в сфері охорони здоров’я. Обґрунтовано доцільність використання інноваційних підходів до організації комунікацій на ринку медичних послуг.Наукова новизна результатів дослідження. Поглиблено концептуальні засади розуміння ролі комунікацій на ринку медичних послуг.Практична значущість результатів дослідження. Сформульовані теоретичні підходи щодо удосконалення комунікаційної діяльності медичних установ можуть стати основою для подальших наукових досліджень і дискусій та дають підґрунтя для реалізації інноваційних підходів до організації комунікацій на ринку медичних послуг.Ключові слова: медичні послуги, ринок медичних послуг, комунікації, комунікаційна діяльність, інновації, телемедицина.  Kotys N.V., Matsyk V.O. INNOVATION APPROACHES TO THE ORGANIZATION OF COMMUNICATIONS AT THE MARKET OF MEDICAL SERVICESPurpose. The aim of the article is to generalize the essence, place and features of communications in the market of medical services and to substantiate the feasibility of using innovative approaches to the organization of communication activities of health care institutions.Methodology of research. The theoretical and methodological basis of the article is the fundamental provisions of modern economic science. The following methods were used in the research process: theoretical generalization and scientific abstraction – when substantiating the categorical-conceptual research apparatus; system analysis – when forming the theoretical and methodological base and research structure; the method of comparative analysis – when identifying regularities and spatial differences in the organization of communications of medical institutions; methods of descriptive statistics and visual analysis – for a visual presentation of the main provisions of the study; descriptive and conceptual modelling - to represent the complex system of communications of a health care institution; of the experiment - to test substantiated and developed innovative approaches to the organization of communications in the market of medical services.Findings. The article focuses on the growing role of communications in the market of medical services. The essence and features of medical services are defined. The principles of the formation of the domestic market of medical services are identified and its specifics are analysed. The personalities of medical communications and communication problems of health care institutions are determined. Trends in the development of modern communication technologies in the field of health care are analysed. The expediency of using innovative approaches to the organization of communications in the market of medical services is substantiated. Recommendations on improving communications by health care institutions are provided.Originality. The conceptual foundations of understanding the role of communications in the market of medical services have been deepened. Scientific and methodological recommendations on the use of innovative approaches to the organization of communications in the market of medical services have been improved.Practical value. The practical significance of the conducted research is that the formulated theoretical approaches and recommendations for improving the communication activities of medical institutions can become the basis for further scientific research and discussions and provide a basis for the implementation of innovative approaches to the organization of communications in the market of medical services.Key words: medical services, market of medical services, communication, communication activities, innovations, telemedicine.
Keywords: медичні послуги; ринок медичних послуг; комунікації; комунікаційна діяльність; інновації; телемедицина